If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 3 + 6x Solving 15 = 3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 15 + -6x = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 15 + -6x = 3 + 0 15 + -6x = 3 Add '-15' to each side of the equation. 15 + -15 + -6x = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -6x = 3 + -15 -6x = 3 + -15 Combine like terms: 3 + -15 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| x^2+10x+4=10 | | 3x+7=-26-8x | | 5z^2+6z+14=0 | | -4+4a=12 | | 3(x-1)-(4x-5)=2(5x-1)-7 | | 52y-29=10 | | 5-(2x+5)=4+4(x+2) | | 12+5n=32 | | x^2+10x-4=10 | | 2q-4=26 | | 115=5t | | -9v-9=-27 | | x^2-13+6x=0 | | -15+10y=25 | | t^2-6t+10=0 | | -30p-2=58 | | 9(5x-2)=32 | | x*12-213=x*4-5 | | p^2-4p-1=0 | | -30-2=58 | | x^2=6x-13 | | 47-7x=2x+19 | | 14+14p=21 | | 7n+(5n+15)=32 | | 140-5x=6x+19 | | 4lnx+lnx^3-lny=lna | | .2x-.5=.5-.2(2x-13) | | 6x+6=126-6x | | Q*3=-4 | | x^2-8x-48=0 | | 1+6x=51+x | | n^2-n=2 |